LEARNING STRATEGY AND INTERLANGUAGE ERRORS: A Case Study of SMPN 5 Padang Panjang Students - Rezy Anggraini (English Language Teaching and Research, 2018)
This study describes learning strategies in relation to interlanguage er- rors. Interlanguage errors are believed as the result of cognitive mechanism or learning strategy used by second language learners. This study specifically describes learning strategies employed by SMPN 5 Padang Panjang students which result in interlanguage errors. The data are sentences containing errors taken from students’ compositions. The result indicates that there are three major types of learning strategy used by the learners, including: overgeneralization, first language transfer, and simplification. Of these, the dominant learning strategy is overgeneralization which implies that the students have relied their linguistic knowledge on the target language (English) rather than on that of their first language. English teachers should have positive attitude on interlanguage errors since errors are an inevitable process in foreign language learning. They must also provide appropriate training for the students so that they are aware the differences between English and Indonesian. Such understanding could help them minimize errors and hence they will be able to develop their interlanguage system. Keywords: interlanguage errors, learning strategy